DAMPAK KEBIJAKAN PEMBANGUNAN WILAYAH BARAT CINA TERHADAP MASYARAKAT TIBET - , AULIA ARYOTEJO ([Yogyakarta] : Universitas Gadjah Mada, 2014)
As one of the country which having a relatively fast economic growth, China is considered to be an economic miracle. Despite of it, thereâs one side that remains to be an obstacle for them which is the economic gap of western and eastern regions. In 2000, Chinaâs Government implement Western Development Policy in order to reduce the gap between western and eastern regions. This policy is being implemented in twelve provincial-level which of consists five autonomous region, six provinces, and one municipality. Tibetan Autonomous Region is one of the area which being covered by the Western Development Policy. This policy is being implemented by the Chinese Government in order to grow the economic of Tibet which was underdeveloped than the other regions. The completion of Qinghai-Tibet railways âone of the project of western development policy- in 2005 led to Tibetâs economic growth and work opportunities for either Tibetan and Chinese migrant. This economic boom that happens in Tibet though can not be absorbed well by the majority of Tibetans because most of them are still living in a traditional ways and their low human resource level made them difficult to compete with the Chinese migrants for work in an economic boom that Tibet enjoyed. This could lead to dissatisfaction of Tibetan because the width of the welfare gap that occurs in Tibet could still being widen. This can be a major setback for Beijing to maintain order in Tibet.